2014
DOI: 10.1016/j.neuroimage.2014.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Occipital and orbitofrontal hemodynamics during naturally paced reading: An fNIRS study

Abstract: Humans typically read at incredibly fast rates, because they predict likely occurring words from a given context. Here, we used functional near-infrared spectroscopy (fNIRS) to track the ultra-rapid hemodynamic responses of words presented every 280 ms in a naturally paced sentence context. We found a lower deoxygenation to unpredictable than to predictable words. The greater hemodynamic responses to unexpected words suggests that the visual features of expected words have been pre-activated previous to stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 92 publications
(143 reference statements)
4
16
0
Order By: Relevance
“…Thus, Bohrn et al (2012b) observed data compatible with the interpretation that anti-proverbs evoking two contrasting responses that have to be related (that of the familiar proverb and the novel word), required a greater semantic integration effort, as mirrored by stronger ventral inferior frontal gyrus activation than for control stimuli (much as with the aforementioned bivalent NNCs; Forgács et al, 2012; Kuhlmann et al, 2016). Moreover, concurrent increased medial orbitofrontal cortex and striatal activation likely reflected the rewarding aspect of successful semantic integration (a kind of “Aha” experience; Bar et al, 2006; Hofmann et al, 2014) and supports both the findings and views of the naturalizing aesthetics studies discussed above.…”
Section: Multiword Expressionssupporting
confidence: 79%
“…Thus, Bohrn et al (2012b) observed data compatible with the interpretation that anti-proverbs evoking two contrasting responses that have to be related (that of the familiar proverb and the novel word), required a greater semantic integration effort, as mirrored by stronger ventral inferior frontal gyrus activation than for control stimuli (much as with the aforementioned bivalent NNCs; Forgács et al, 2012; Kuhlmann et al, 2016). Moreover, concurrent increased medial orbitofrontal cortex and striatal activation likely reflected the rewarding aspect of successful semantic integration (a kind of “Aha” experience; Bar et al, 2006; Hofmann et al, 2014) and supports both the findings and views of the naturalizing aesthetics studies discussed above.…”
Section: Multiword Expressionssupporting
confidence: 79%
“…Penolazzi et al, 2007;Sereno and Rayner, 2003;Skrandies, 1998). A recent optical imaging study using the same experimental design confirmed the hypothesis that this results from occipital cortex activation (Dambacher et al, 2009;Hofmann et al, 2014). A potential explanation is that expectations generated at a semantic level feed activation back to the lowest level of feature representations in the occipital cortex (cf.…”
Section: Iams and The Ventral Visual Streammentioning
confidence: 59%
“…This function of a process model has been the traditional role and strength of IAMs since their initial proposal. In sum, the novel level of semantic representations in the AROM extends IAMs of visual-orthographic processing by the mechanism of associative spreading of activation between semantic word units (Anderson, 1983;Collins and Loftus, 1975): If there is enough excitation from associated items or common associates in the experimental context, a word unit can become pre-activated (Hofmann et al, 2014).…”
Section: Quantifying Semantics In Iamsmentioning
confidence: 91%
“…His poem “ O Heimat, zynischer Euphon” (O homeland, zynical euphon) is supposed to be a case in point (Ganseuer, 2006). Indeed, all other things being equal, the amplitude of the N400 decreases with increasing predictability of a word in a sentence, idiom, or story (e.g., Van Berkum et al, 2005; Dambacher et al, 2006, 2009, 2012; Vespignani et al, 2009), an effect that recently was replicated using fNIRS (Hofmann et al, 2014). Both eye tracking and EEG methods can be combined to provide a more ecologically valid means of studying literature reception, but the methodology is still not fully developped (Hutzler et al, 2007; Dimigen et al, 2011).…”
Section: Assessing Fg Features and Esthetic Processes (Jakobson’s Poementioning
confidence: 91%